Addition of the combination of sims technique and semi-fowler positioning to cardiorespiratory exercises in patients with myasthenia gravis: case report - Raini, Putu Ayu Meka; Sundari, Luh Putu Ratna; Fridayani, Ni Kadek Yuni (International Journal of Research in Medical Sciences, 2021)
Myasthenia gravis (MG) is an autoimmune disorder characterized by fluctuating muscle fatigue, worsening with increased activity, and improving at rest. Physiotherapy plays a role in reducing symptoms such as shortness of breath, respiratory muscle weakness, and airway obstruction due to decrease the sputum in the lung lobes and prevent of the exacerbation. Respiratory training and postural drainage techniques are part of intervention that given by physiotherapy for patients diagnosed with MG and had symptoms hospital acquired pneumonia (HAP). A male, 28 years old patient diagnosed with HAP and had history of MG hospitalized a month with dyspnoea and disable to do activity daily living. Physiotherapy treatment that given to the patient from 18th July 2018 till 28th July 2018 are respiratory training included breathing exercise, cough exercise, shoulder expansion, Active Range of motion (ROM) exercise, stretching of respiratory muscle and home program exercise that helped by nurse and caregiver. Patient had medical treatment from all medical team by pulmonologist, neurologist and nurse too. Combined this new technique postural drainage and all physiotherapy programs showed significant in patient such as dyspnoea decreased.